Co-transcriptional commitment to alternative splice site selection. - Roberts, G C (1998)
Production of mRNA in eukaryotic cells involves not only transcription but also various processing reactions such as splicing. Recent experiments have indicated that there are direct physical connections between components of the transcription and processing machinery, supporting previous suggestions that pre-mRNA splicing occurs co-transcriptionally. Here we have used a novel functional approach to demonstrate co-transcriptional regulation of alternative splicing. Exon 3 of the alpha-tropomyosin gene is specifically repressed in smooth muscle cells. By delaying synthesis of an essential downstream inhibitory element, we show that the decision to splice or repress exon 3 occurs during a limited window of opportunity following transcription, indicating that splice site selection proceeds rapidly after transcription.